Analisis Keserasian Alat Gali Muat dan Angkut Batubara Dalam Produksi Overburden Di Pit Alam 1-3 Di PT. Muara Alam Sejahtera, Kabupaten Lahat, Sumatera Selatan - Ari Dwi Ananda; Harizona Aulia Rahman; Heri Prabowo (Departemen Teknik Pertambangan FT UNP, 2023)
Excavation equipment is loaded by excavators and transported by coal dump trucks from the mining front to the stockpile and transportation of overburden to the disposal. Smooth production must of course be supported by the type of excavator with the appropriate bucket capacity of the dump truck used so that there is no queue so that coal production is in accordance with the plan and is more efficient for using production equipment and affects costs later. Coal excavation-loading equipment production on Hitachi ZX350 LC excavator in one month amounted to 95.984 tons / month. And the production of Dongfeng Tianlong KC 4 × 6 dump truck conveyance in one month is 14.953 tons / month.The production of overburden excavation tools on the XCMG XE-1250 excavator in one month amounted to 194.548,73 Bcm / month. And the production of LGMG CMT 106 conveyance in one month amounted to 21.843,5 Bcm / month. To make the match factor value = 1.00 or close to 1.00, it is better to reduce it to 9 conveyance tools (dump trucks) only (obtained value = 1.01) for the overburden loading and unloading travel process to the disposal area. And for coal equipment loading and unloading travel, namely the addition of conveyance tools (dump trucks) is needed to be 6 dump trucks (obtained value 0.93) in order to achieve compatibility of excavation-loading tools so that transportation and efficient use of tools.